HUBUNGAN ANTARA CARA MENGGOSOK GIGI TERHADAP KEJADIAN KARIES GIGI PADA ANAK USIA SEKOLAH - Rahayu Efendi; Arneliwati Arneliwati; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dental health problems are a health problem that requires comprehensive treatment, because dental problems have abroad impact covering physical, mental and social factors for individuals suffering from dental disease. This study aimsto determine the relationship between how to brush teeth on dental caries events in school-aged children with researchdesign of observational analysis and cross sectional approach. The sample of this research is 51 respondents takenbased on sampling total sampling technique. Data analysis used chi-square test. The data were collected usingobservation sheet and caries examination on Molar I teeth. The result showed that way of brushing respondents teethwas not good as much 35 students (68,6%) and good category as much as 16 students (31,4%), students with dentalcaries as many as 37 students (72.5%) did not dental caries 14 students (27.5%). The result of statistical test obtained pvalue = 0,005 <α (0,05), so it can be concluded that there is a significant relationship between the way of brushingteeth to the incidence of dental caries in school age childrenKeywords : Dental caries, how to brush teeth,school-age children